Relative adrenal insufficiency in severe acute variceal and non‐variceal bleeding: influence on outcomes. (10th February 2015) - Graupera, Isabel; Pavel, Oana; Hernandez‐Gea, Virginia; Ardevol, Alba; Webb, Susan; Urgell, Eulalia; Colomo, Alan; Llaó, Jordina; Concepción, Mar; Villanueva, Càndid
Abstract Background & Aims Relative adrenal insufficiency (RAI) is common in critical illness and in cirrhosis, and is related with worse outcomes. The prevalence of RAI may be different in variceal and non‐variceal bleeding and whether it may influence outcomes in these settings is unclear. This study assesses RAI and its prognostic implications in cirrhosis with variceal bleeding and in peptic ulcer bleeding. Methods Patients with severe bleeding (systolic pressure <100 mmHg and/or haemoglobin <8 g/L) from oesophageal varices or from a peptic ulcer were included. Adrenal function was evaluated within the first 24 h and RAI was diagnosed as delta cortisol <250 nmol/L after 250 μg of i.v. corticotropin. Results Sixty‐two patients were included, 36 had cirrhosis and variceal bleeding and 26 without cirrhosis had ulcer bleeding. Overall, 15 patients (24%) had RAI, 8 (22%) with variceal and 7 (24%) with ulcer bleeding. Patients with RAI had higher rate of bacterial infections. Baseline serum and salivary cortisol were higher in patients with RAI (P < 0.001) while delta cortisol was lower (P < 0.001). There was a good correlation between plasma and salivary cortisol (P < 0.001). The probability of 45‐days survival without further bleeding was lower in cirrhotic patients with variceal bleeding and RAI than in those without RAI (25% vs 68%, P = 0.02), but not in non‐cirrhotic patients with peptic ulcer bleeding with or without RAI (P = 0.75). Conclusion The prevalence of RAI is similar in ulcer bleeding and in cirrhosis with variceal bleeding. Cirrhotic patients with RAI, but not those with bleeding ulcers, have worse prognosis.